Detection of blood volumes and haemoglobin mass by means of CO re-breathing and indocyanine green and sodium fluorescein injections. (3rd April 2017) - Keiser, Stefanie; Meinild-Lundby, Anne-Kristine; Steiner, Thomas; Trösch, Severin; Rauber, Sven; Krafft, Alexander; Burkhardt, Tilo; Hilty, Matthias Peter; Siebenmann, Christoph; Wehrlin, Jon Peter; Lundby, Carsten
Abstract: The main aim of the present study was to quantify the magnitude of differences introduced when estimating a given blood volume compartment (e.g. plasma volume) through the direct determination of another compartment (e.g. red cell volume) by multiplication of venous haematocrit and/or haemoglobin concentration. However, since whole body haematocrit is higher than venous haematocrit such an approach might comprise certain errors. To test this experimentally, four different methods for detecting blood volumes and haemoglobin mass (Hbmass ) were compared, namely the carbon monoxide (CO) re-breathing (for Hbmass ), the indocyanine green (ICG; for plasma volume [PV]) and the sodium fluorescein (SoF; for red blood cell volume [RBCV]) methods. No difference between ICG and CO re-breathing derived PV could be established when a whole body/venous haematocrit correction factor of 0.91 was applied ( p  = 0.11, r  = 0.43, mean difference −340 ± 612 mL). In contrast, when comparing RBCV derived by the CO re-breathing and the SoF method, the SoF method revealed lower RBCV values as compared to the CO re-breathing method ( p  < 0.05, r  = 0.95, mean difference −728 ± 184 mL). However, compared to the ICG and the SoF methods, the typical error (%TE) and hence reliability of the CO re-breathing method was lower for all measured parameters. Therefore, estimating blood volume compartments by the direct assessment of another compartment can be considered a suitable approach. The CO re-breathing method proved accurate in determining the induced phlebotomy and is at the same time judged easier to perform than any of the other methods.